Effect of x on the electrochemical performance of two-layered cathode materials xLi2MnO3–(1−x) LiNi0.5Mn0.5O2 - Díaz Desposorio, Félix Napoleón (2022)
In our study, the cathodic material xLi2MnO3–(1−x)LiNi0.5Mn0.5O2 was synthesized by means of the co-precipitation technique. The effect of x (proportion of components Li2MnO3 and LiNi0.5Mn0.5O2 ) on the structural, morphological, and electrochemical performance of the material was evaluated. Materials were structurally characterized using X-ray diffraction (XRD), and the morphological analysis was performed using the scanning electron microscopy (SEM) technique, while charge–discharge curves and differential capacity and impedance spectroscopy (EIS) were used to study the electrochemical behavior. The results confirm the formation of the structures with two phases corresponding to the rhombohedral space group R3m and the monoclinic space group C2/m, which was associated to the components of the layered material. Very dense agglomerations of particles between 10 and 20 µm were also observed. In addition, the increase in the proportion of the LiNi0.5Mn0.5O2 component affected the initial irreversible capacity and the Li2MnO3 layer’s activation and cycling performance, suggesting an optimal chemical ratio of the material’s component layers to ensure high energy density and long-term durability.